Effect of prey on predation, growth and biology of green lacewing (Chrysoperla zastrowi sillemi) - SATPATHY, S; KUMAR, AKHILESH; SHIVALINGASWAMY, T M; RAI, A B (The Indian Journal of Agricultural Sciences, 2012)
The larvae of the polyphagous predator, green lacewing [Chrysoperla zastrowi sillemi (Esben-Petersen)] was reared on natural prey including cabbage aphid (Brevicoryne brassicae), bean aphid (Aphis craccivora), nymphs of okra jassid (Amrasca biguttula biguttula), eggs and neonate larvae of Spodoptera litura and eggs of Corcyra cephalonica to study the effect of prey regimes on the predation and the biology of the predator. The lacewing grub preyed significantly highest number of prey units (415.50 eggs/ grub) of C. cephalonica eggs which was significantly more than the S. litura eggs (250.60 eggs/ grub), A. biguttula biguttula (185.00 nymphs/ grub), B. brassicae (127.50 aphids/grub), A. craccivora (119.00 aphids/grub) and neonates of S.litura (62.25 larvae/grub). The larval duration varied from 7.50 to 15.235 days on different preys which was seven day less in the grubs reared on eggs than the grubs fed on insect as prey. Larval survival was significantly highest (97.82%) on C. cephalonica eggs. The pupal period varied from 7.50 days to 8.63 days. The grubs reared on eggs of C. cephalonica and S. litura showed longer pupal period. On insects as prey, the growth index (GI) of larvae was significantly less (5.56–8.58) compared to the larvae reared on egg-hosts. The weight of grubs preying on other hosts was 35–50% less compared to those reared on C. cephalonica eggs. Relative inadequacy of lepidopteran neonates and aphids except B. brassicae as prey for the young larvae adversely affected the larval survival, GI and adult emergence may be due to reduced nutritional support exerting adverse effect on growth and causing moulting distress.